Chronic Kidney Disease and Risk of Glaucoma: A Case-Control Study (Journal of Preventive and Social Medicine, 2025)
Background: Glaucoma and chronic kidney disease (CKD) are major global health concerns with shared pathophysiological mechanisms including oxidative stress, inflammation, and microvascular damage. Despite growing evidence of their bidirectional relationship, limited research exists on their association in developing countries like Bangladesh. This study aimed to assess the association between chronic kidney disease and glaucoma risk among patients in Bangladesh. Methods: A case-control study was conducted at National Institute of Ophthalmology and Bangabandhu Sheikh Mujib Medical University, Dhaka, from July 2023 to June 2024. The study included 115 physician-diagnosed glaucoma cases and 115 age- and sex-matched controls without glaucoma. Data were collected through structured interviews and medical record reviews. Multivariable logistic regression was performed to determine adjusted odds ratios (AOR) while controlling for potential confounders. Results: CKD prevalence was significantly higher among cases (53.0%) compared to controls (13.0%, p